Effect of milling method and time on the properties and electrochemical performance of LiFePO4/C composites prepared by ball milling and thermal treatment - Zhang, D.; Cai, R.; Zhou, Y.; Shao, Zongping; Liao, X.; Ma, Z. (Pergamon, 2010)
Effects of ball milling way and time on the phase formation, particulate morphology, carbon content, and consequent electrode performance of LiFePO4/C composite, prepared by high-energy ball milling of Li2CO3, NH4H2PO4, FeC2O4 raw materials with citric acid as organic carbon source followed by thermal treatment, were investigated. Three ball milling ways and five different milling durations varied from 0 to 8 h were compared. LiFePO4/C composites could be obtained from all synthesis processes. TEM examinations demonstrated LiFePO4/C from ball milling in acetone resulted in sphere shape grains with a size of ~60 nm, similar size was observed for LiFePO4/C from dry ball milling but in a more irregular shape. The ball milling in benzene resulted in a much larger size of ~250 nm. The LiFePO4/C composites prepared from dry ball milling and ball milling in acetone showed much better electrochemical performance than that from ball milling in benzene. SEM examinations and BET measurements demonstrated that the high-energy ball milling effectively reduced the grain size. A ball milling for 4 h resulted in the best electrochemical performance, likely due to the proper amount of carbon and proper carbon structure were created. © 2009 Elsevier Ltd. All rights reserved.